2019
DOI: 10.1177/2042098619882819
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quantitative signal detection in EudraVigilance for orphan drugs: possible risk of false negatives

Abstract: Different strategies have been studied to allow a better characterization of the safety profile of orphan drugs soon after their approval. At the end of the development phases only few data are available because of the small number of subjects exposed to an orphan medicine for the treatment of rare or ultra-rare conditions. As a consequence, the evaluation of the safety profile is limited at the time of the first approval. In the post-marketing period, all available sources should be combined for a better unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…Their natural incidence ranges from 56 events per 100,000 persons to 182 events per 100,000 persons which should be considered against the three deaths from PE in 17 million following vaccination [16,17]. A recent single study from Croatia reported an increase in prevalence of 'combined DVT with PE but not with isolated PE or isolated DVT' [18]. The authors noted from their comparison of non-Covid-19 patients in matched 8-month periods in 2019 pre-and in 2020 during the pandemic a significantly older age group admitted to hospital (60.8 ± 17.2 years v. 68.5± 16.8 years) [18].…”
Section: Resultsmentioning
confidence: 99%
“…Their natural incidence ranges from 56 events per 100,000 persons to 182 events per 100,000 persons which should be considered against the three deaths from PE in 17 million following vaccination [16,17]. A recent single study from Croatia reported an increase in prevalence of 'combined DVT with PE but not with isolated PE or isolated DVT' [18]. The authors noted from their comparison of non-Covid-19 patients in matched 8-month periods in 2019 pre-and in 2020 during the pandemic a significantly older age group admitted to hospital (60.8 ± 17.2 years v. 68.5± 16.8 years) [18].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is important to detect rare AEs through post-marketing surveillance studies. However, traditional methods are not sensitive enough to detect rare AEs, resulting in false negatives ( Sardella and Lungu, 2019 ). Hence, several regulatory authorities recommend that DPAs be complemented with other appropriate methods to identify rare safety signals ( Kimura et al, 2011 ; Jos, 2015 ; Hesha, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…All contributing parties should make these data available in an unbiased manner. Identification of new safety signals is specifically important for orphan drugs where the experience is still limited at the time of approval [35]. Therefore, any new safety signal should not only be communicated with clinical trial sites but with all treatment centres.…”
Section: Strength Of Consensus: Strong Consensus (100%)mentioning
confidence: 99%